A plain introduction to the criticism of the New Testament for the use of Biblical students - Scrivener, Frederick Henry Ambrose, 1813-1891 (Cambridge, Uk Deighton, Bell and co, 1874)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. -- criticism, interpretation, etc